Generation of clean water in dry deserts based on photo-voltaic solar plants - María del Carmen Emilia Ancaya-Martínez; Freddy Antonio Ochoa Tataje; Jannett Maribel Flórez-Ibarra; Ricardo Manuel Arias Velásquez, PhD. (Ain Shams Engineering Journal, 2022)
In Latin America the renewable energy has increased in 40GW, during the last twenty years; in this perspective countries as Perú, Chile, Brazil, Bolivia and Colombia have extensive desert with the highest irradiance and large field available for this technology. One example is the Atacama Desert and its extension in Chile and Peru; however, it has some challenges as the water availability. Therefore, the clean water availability for industry and agriculture is a problem, only 2.5% of the world's water is fresh water, this value is decreasing every year for agriculture and industrial process. Our methodology has been applied during 2019 to 2021 with a real case study, one water machine has generated 128,000 L of water per year, >230% of efficiency compared with traditional techniques with the same energy consumption: its contribution with a correlational study of 92.33%.